Pancasila sebagai Karya Estetis Bangsa Indonesia: Sebuah Refleksi Filosofis - Doweng Bolo, Andreas (Faculty of Philosophy, Parahyangan Catholic University, Bandung, 2011)
Pancasila is the nation's art in Indonesia, that is, a masterpiece rooted in the values that have been grown in the society. Since it has been embedded in the society, the values it gives rise should be returned to the society. It is worthy to say that Pancasila is the substantial values of this nation, without which Indonesia will disperse. This value tracing is in fact not a finished work, but an ongoing process. Thus the language used to translate the values ought to be unique, communicative, and contextual. To the end that the language contextual, the learning of local cultural values is an important orientation since only with it Pancasila has a future in this nation. When Pancasila deters the values emerging from the local wisdom then something is definitely wrong there, for these values are the root of Pancasila. Pancasila enriches the local virtues and vice versa. Because Pancasila was formulated from the local virtues then it must also be returned using the local, contextual and hospitabe language. Dogmatic and unsocial language based on the Cartesian patterns that is used to put this ideology into practice needs to be recolored. In this paper, an aesthetic paradigm is reconsidered to make room for experiences. Pancasila should be approached in a language that grew out of the sense of awe. When we talk about awe, we talk about how to talk aesthetically. Being amazed by this spirit is a start to walk through the journey towards being Indonesia. Departing from this aesthetic paradigm, the author examines the spirits that already exist and grow in the societies. Keywords:*Aesthetics, *Pancasila, *experience, *aesthetic experience, *awe, *diversity, *local values, *contextual language, *aesthetic masterpiece, *familial and common experiences, *culturization